Optimized Production Of Poly(3-Hydroxybutyrate) And Poly(3-Hydroxybutyrate-Co-4-Hydroxybutyrate) By Cupriavidus Sp. Usmaa2-4 In A One-Stage Fermentation - Md Iqbal, Nurhezreen (2013)
Polyhydroxyalkanoate (PHA) is a biodegradable and biocompatible thermoplastic synthesized by microorganisms as intracellular energy and carbon reserved materials. P(3HB) homopolymer is stiff and brittle while P(3HB-co-4HB) copolymer have properties ranging from crystalline to rubber-like materials which correlates with the changes in the 4HB monomer compositions. In addition, the degradation products of P(3HB-co-4HB) is non toxic and biocompatible to human body, as the degradation product of both monomers is a natural metabolite present in mammalian body.